The Analysis of Bandung University Students' Ability in Identifying Hoaxes - Chairunnisa Kamilah; Nur Atnan (Universitas Muhammadiyah Sidoarjo, 2021)
Technological sophistication makes all forms of information available through social media. Information on social media can be uploaded by anyone who owns an account on the social media. This makes many individuals who falsify information for personal or group interests. This study aims to find out whether Bandung Raya students who live in urban areas and are accustomed to accessing social media are able to assess whether the content or articles they see are hoaxes or not. This study uses descriptive quantitative methods by conducting surveys through distributing questionnaires and collecting answers from respondents, namely Bandung Raya students. Data collection was carried out in this study using a questionnaire distributed via google form to 100 samples of students studying in the Bandung Raya area. Based on the results of the analysis that has been carried out on the five indicators to identify hoaxes, the total score of the 22 questions asked is 6,685 and a percentage of 75.96% which is then entered into the continuum line so that it falls into the